(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The article is devoted to the lexical features of the Arabic language, its problems and solutions. It describes the lexical units of the Arabic language and their peculiarities. There is also a special emphasis on word formation in Arabic. Since Arabic belongs to the family of inflected languages, the formation of a new word in it is done not by adding to the base, but by replacing, increasing or decreasing the letters in the core letters. Terms such as core and supplement are also explained below, and various scientific bases are given. Special attention is paid to the use of lexical units (words and phrases), semantic features, synonyms and antonyms